(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
Language skills are the cornerstone of effective communication, encompassing listening, speaking, reading, and writing. Each skill is vital for personal, academic, and professional success, and they are interrelated, with each supporting the development of the others. This article provides an overview of these four fundamental skills, discusses their importance, and explores various methods and technologies for their development. By integrating different approaches, learners can enhance their language proficiency and achieve comprehensive communication abilities.